Biodegradation as natural fibre pre-treatment in composite manufacturing. Issue 1 (14th March 2016) - Sotenko, Maria; Coles, Stuart R.; McEwen, Iain; DeCampos, Rejane; Barker, Guy; Kirwan, Kerry
Abstract : Bacterial and fungal degradation of wheat straw has become intensively scrutinised in recent years because of the growing interest in procuring useful feedstocks and chemicals from lignocellulosic sources. Typically, after the extraction of valuable sugars and phenolics, significant quantities of solid biomass remain as waste. In this work, it has been shown that the leftover fermented wheat straw can be successfully used to reinforce epoxy resins, providing better strength properties compared to non-degraded straw. A 12% and a 22% increase in Young's modulus and ultimate tensile strength respectively were observed for degraded wheat straw/epoxy composites compared to composites containing non-degraded straw. The improvement in mechanical strength is explained in terms of the structural and morphological transformations that occurred in the fibres during the fermentation process. The opportunity to use degraded natural fibres in the manufacturing of composites, in addition to the production of chemicals from lignocellulosic feedstocks, looks promising for improving biorefinery economics further.